The clinical burden of potentially inappropriate medications on hospitalization risk in an Italian older adult cohort: a large-scale real-world study - Andrea Rossi; Elena Olmastroni; Gerard Ompad; Manuela Casula; Maurizio Sessa (International Journal of Pharmacy Practice, 2026)
Abstract Introduction Optimizing drug treatments in older adults is essential for improving health outcomes and reducing drug-related issues. Objective This study aimed to develop an updated and comprehensive explicit indicator of potentially inappropriate medications in older adults, and to evaluate its association with all-cause hospitalization. Methods Administrative healthcare data from Local Health Units (LHUs) in Lombardy, Italy (2015–2018) were used to identify individuals aged ≥65 years who were exposed to potentially inappropriate medications (PIMs), identified through an explicit criteria-based list. Risk-set matching was used to select unexposed controls, and logistic regression models adjusted for high-dimensional propensity scores were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for all-cause hospitalization within 90 days after the first exposure date. Key findings Among 641 230 older patients, between 52.8% and 56.3% were exposed to at least one PIM. After matching (128 063 pairs) hospitalization rates were higher among the exposed (8.3%–10.2%) compared with the not exposed (5.1%–6.0%) across the LHUs. Pooled estimates showed an increased risk of hospitalization for those exposed (ORs 1.55, 95% CIs 1.48–1.62), with the highest risk observed in adults aged 65–74 years (1.67, 1.59–1.76) and in women (1.62, 1.55–1.70). Conclusions Over half of older individuals were exposed to at least one PIM, with a 55% increase in short-term hospitalization risk. These findings highlight the urgent need for improved prescribing practices tailored to older populations.